The Talent Profit Chain : A Case Study of Bangladesh on Talent Management and Productivity as a New Way of Calculating Economic Profit - Ashraf, Mohammad (International Research Journal of Business Studies, 2009)
In many businesses today, economies of scale do not exist; rather there are economies of ideas and talents. Against this new reality, the present study proposes an interesting and inevitable phase of the economy of managing talents surpassing the economy of staging experience that is traversed ---from extracting commodities to making goods to delivering services. Manage talents facilitate innovations that induce added value and productivity in both demand and supply sides of the economy. It also introduces a new way of calculating economic profit incorporating a compact of talent management intertwined the elements of brand, purpose, opportunity and culture. In the end, the study reviews a case of agro-enterprise in Bangladesh that suggests that the firms which are talent-oriented they are more productive or more profitable in compare to other firms which are capital-oriented. Hence, the research concludes that manage talents are the latest phase of economy of 21st century’s management which nurtures economies of talent rather than economies of scale in calculating and maximizing profit.